Bacterial Etiology and Antibiotic Sensitivity Pattern of Community Acquired Pneumonia in Diabetic Patients: Experience in a Tertiary Care Hospital in Bangladesh - Ahmed, Jamal Uddin; Hossain, Mohammad Delwar; Rahim, Muhammad Abdur; Afroz, Farhana; Musa, AKM (BIRDEM Medical Journal, 2017)
Background: Diabetes mellitus (DM) is an immunosuppressive condition and uncontrolled diabetes is associated with increased susceptibility to various infections like pneumonia. Community acquired pneumonia (CAP) in diabetic patients is often caused by more virulent or atypical organisms and associated with increased resistance to conventional antibiotics. The aims of this study were to identify the bacterial etiology of CAP in patients with DM and to see their antibiotic sensitivity pattern. Methods: This was a cross-sectional, observational study conducted in the Department of Internal Medicine & Pulmonology of BIRDEM General Hospital, Dhaka, Bangladesh, from January 2013 to December 2015. A total of 120 hospitalized diabetic patients diagnosed with CAP and with a positive sputum culture growth of any bacteria were included in the study. Results: Majority (67%) of the patients were male. Mean age of the patients was - 55.69 ±10.5 years. Mean duration of diabetes was - 7.35 ±1.3 years. Mean HbA1c was - 8.6 ±1.89%. Sputum for culture showed that out of 120 (100%) patients, Klebsiella pneumoniae was detected in 53 (44.2%) patients, Staphylococcus aureus in 18 (15.0%), Pseudomonas species in 16 (13.3%) patients, Acinetobacter in 10 (8.3%), Escherichia coli in 9 (7.5%) patients and 14 (11.7%) patients had growth of other organisms. Sensitivity pattern of different bacterial growth in sputum to commonly used antibiotics like ceftriaxone, ciprofloxacin, amikacin and imipenem were as follows Klebsiella (19%, 47%, 74%, 96% respectively), Staph aureus (11%, 33%, 78%, 67% respectively), Pseudomonas (19%, 75%, 81%, 88% respectively), Acinetobacter (0%, 0%, 20%, 50% respectively), E. coli (22%, 22%, 100%, 100% respectively). All (100%) of the Pseudomonas and Acinetobacter were sensitive to colistin. Most of the growth of all the bacteria (Klebsiella 94%, Staphylococcus 78%, Pseudomonas 81%, Acinetobacter 100%, E. coli 100%) occurred in patients with poor glycemic control (HbA1c ? 7.0%). Conclusion: This study results suggest that CAP in diabetic patients are more frequently due to Klebsiella pneumoniae, Staphylococcus aureus and Pseudomonas species and mostly they are less sensitive to commonly used antibiotics like ceftriaxone and ciprofloxacin. So, whenever possible, treatment of CAP should be guided by sputum culture and sensitivity test and for empirical treatment of CAP in diabetic patients, alternative antibiotics like imipenem and amikacin should be considered. Birdem Med J 2017; 7(2): 101-105